Stigmatizing and Excluding HIV/ AIDS Patients Through Language in Cameroon - Safotso, Gilbert Tagne (Advances in Social Sciences Research Journal, 2017)
Over the past thirty years, the world has been struggling to combat HIV/ AIDS, which in some parts of the globe, rather continues to cause serious ravages. In Cameroon, where the rate of infection ranges from four to seven per cent, depending on the region, a rich coded language has developed to discuss this disease. This paper examines that language to show how it contributes to stigmatize and exclude HIV/ AIDS patients. Results of data collected through informal talks and questionnaire (N=200), reveal that Cameroonians generally use euphemistic language to stigmatize and ostracise those who suffer from this epidemic. The paper concludes by proposing some positive language which can help ease the sufferings and integrate this group of marginal citizens, for their better contribution in the development of the country.